Method and workpiece for improving wear resistance of robot ankle by 3D printing

By controlling the diameter and scanning spacing of the laser beam in 3D printing technology, the columnar position error sub -cry is formed, which solves the problem of component wear resistance in the existing technology. Once for forming control and extension of service life.

CN117282985BActive Publication Date: 2025-01-24ZHEJIANG LAB
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311396784.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-25
Publication Date
2025-01-24
Estimated Expiration
2043-10-25

AI Technical Summary

Technical Problem

The wear resistance of parts formed by the existing laser powder bed melting process depends on traditional post-treatment technology, which has problems such as cumbersome process, difficult processing and high cost. Especially for complex structures and special-shaped parts, the traditional post-treatment technology is more applicable. Low.

Method used

Through 3D printing technology, the spot diameter and scanning spacing of the laser beam are controlled to satisfy H=(0.1~0.5)d, which promotes the raw material powder to form columnar dislocation subcrystals and forms continuous and uniformly oriented oblique columnar dislocation subcrystals. Thereby regulating the wear resistance of the printed workpiece.

Benefits of technology

The abrasion resistance of printing workpieces is improved, the service life is extended, and the formation control of the wear resistance of the components is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117282985B_ABST
    Figure CN117282985B_ABST
Patent Text Reader

Abstract

The present application provides a method and workpiece for improving the wear resistance of a robot ankle through 3D printing. The method includes constructing a three-dimensional model of a sample to be printed, slicing the three-dimensional model to obtain the contour boundaries of multiple slice layers, and laying the raw material powder within the contour boundaries of each slice layer; scanning the raw material powder on each slice layer with a laser beam to melt it, and preparing a printed workpiece for preparing a robot ankle; the spot diameter of the laser beam is d, and the scanning spacing of the laser beam on each slice layer is H, satisfying H = (0.1~0.5)d. The printing method provided in the present application can improve the wear resistance of the printed workpiece and extend the service life of the printed workpiece.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of 3D printing technology, and more specifically, to a method and workpiece for improving the wear resistance of a robot ankle through 3D printing. Background Art

[0002] 3D printing is a type of rapid prototyping technology, also known as additive manufacturing. It is a technology that uses digital model files as the basis, uses powdered metal or plastic and other bondable materials to construct objects by printing layer by layer. As one of the most commonly used processes in additive manufacturing, the laser powder bed fusion process (L-PBF) mainly uses the thermal energy of the laser beam to sinter the raw material powder together to form a printed workpiece. The biggest feature of the laser powder bed fusion process is that it can form any complex structure with high precision, and therefore shows great potential in the high-performance, multifunctional design and integrated manufacturing of metal parts.

[0003] However, the wear resistance of parts currently formed by the laser powder bed fusion process still relies on traditional post-processing processes to improve. Integrated high-end parts usually have complex structures. For the post-processing of the wear resistance of complex structures, there are disadvantages such as cumbersome processes, difficult processing and high costs. At the same time, for highly complex special-shaped parts, the applicability of traditional post-processing processes is low. Therefore, how to control the process of laser powder bed fusion, realize the regulation of parts wear resistance, and form metal parts with high wear resistance in one time is one of the problems that need to be solved urgently in metal additive manufacturing. Summary of the invention

[0004] The present application provides a method and a workpiece for improving the wear resistance of a robot ankle through 3D printing. The method can improve the wear resistance of the printed workpiece and extend the service life of the printed workpiece.

[0005] Specifically, the present application is implemented through the following technical solutions:

[0006] On the one hand, the present application provides a method for improving the wear resistance of a robot ankle by 3D printing, comprising:

[0007] Constructing a three-dimensional model of a sample to be printed, slicing the three-dimensional model to obtain contour boundaries of multiple slice layers, and laying raw material powder within the contour boundaries of each slice layer;

[0008] The raw material powder on each slice layer is melted by scanning with a laser beam to obtain a printed workpiece for preparing a robot ankle; the spot diameter of the laser beam is d, and the scanning interval of the laser beam on each slice layer is H, satisfying H=(0.1~0.5)d.

[0009] Optionally, the melting of the raw material powder on the slice layer by scanning the laser beam comprises:

[0010] The raw material powder on the first slicing layer is melted by laser beam scanning to form a first molten pool, and then the raw material powder adjacent to the raw material powder on the first slicing layer is melted by laser beam scanning to form a second molten pool; the overlap rate of the first molten pool and the second molten pool is 80%~95%.

[0011] Optionally, an angle between a scanning path of the laser beam on the first slicing layer and a scanning path of the laser beam on the second slicing layer is 60-90°.

[0012] Optionally, the spot diameter of the laser beam is 60-70 μm; and the scanning interval of the laser beam on each slice layer is 6-35 μm.

[0013] Optionally, the power of the laser beam is 200-220 W; the scanning speed is 740-760 mm / s; the exposure time is 70-90 μs; and the dot pitch is 50-70 μm.

[0014] Optionally, the raw material powder is laid with a layer thickness of 40-60 μm.

[0015] Optionally, the raw material powder includes the following elements in weight percentage: C is 0~0.003%, Ni is 12.5~13%, Mn is 0~2.00%, S is 0~0.01%, P is 0~0.02%, Cr is 17.5~18%, Cu is 0~0.50%, Mo is 2.25~2.5%, and the balance is Fe.

[0016] Optionally, the melting process is performed under an inert atmosphere.

[0017] On the other hand, the present application also provides a printed workpiece, which is printed by any of the above-mentioned printing methods.

[0018] Optionally, the Vickers hardness (HV 0.05 ) is 235~297; the wear resistance of the workpiece is 0.145~1.470 mm 3 / (N·m).

[0019] The technical solution provided by this application can achieve the following beneficial effects:

[0020] The present application provides a method and workpiece for improving the wear resistance of a robot ankle through 3D printing. The method limits the spot diameter d of the laser beam and the scanning spacing H of the laser beam on each slice layer to satisfy H=(0.1~0.5)d, thereby promoting the raw material powder to form columnar dislocation subcrystals, so that the prepared printed workpiece forms continuous and uniformly oriented oblique columnar dislocation subcrystals, thereby changing the ease of plastic deformation of the printed workpiece, realizing the regulation of the wear resistance of the printed workpiece, thereby improving the wear resistance of the printed workpiece and extending the service life of the printed workpiece. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a flow chart of a printing method shown as an exemplary embodiment of the present application.

[0022] Figure 2 A schematic diagram of the scanning path of a laser beam on adjacent slice layers is shown as an exemplary embodiment of the present application.

[0023] Figure 3 This is a top view of the morphological structure of the molten pool formed on two adjacent slice layers at different scanning intervals of the laser beam in Examples 1 to 4 of the present application.

[0024] Figure 4 This is a morphology diagram of the microstructure substructure of the printed workpiece obtained by processing Examples 1 to 4 of the present application and Comparative Example 1.

[0025] Figure 5 This is a hardness test data chart of the printed workpieces obtained by processing Examples 1 to 4 of the present application and Comparative Example 1.

[0026] Figure 6 This is a graph of scratch depth test data of printed workpieces obtained by processing Examples 1 to 4 of the present application and Comparative Example 1.

[0027] Figure 7 This is a test data chart of the wear rate of the printed workpieces obtained by processing Examples 1 to 4 of the present application and Comparative Example 1.

[0028] Figure 8 The microscopic morphology of scratches on the printed workpieces obtained by processing Examples 1 to 4 of the present application and Comparative Example 1 is shown. DETAILED DESCRIPTION

[0029] In order to further understand the present application, the exemplary embodiments will be described in detail below. It should be noted that the protection scope of the present application is not limited by the following embodiments. In the absence of conflict, the technical features in the following embodiments and implementations can be combined with each other.

[0030] like Figure 1As shown, the present application provides a method for improving the wear resistance of a robot ankle by 3D printing, comprising:

[0031] S1, constructing a three-dimensional model of a sample to be printed, slicing the three-dimensional model to obtain contour boundaries of multiple slice layers, and laying raw material powder within the contour boundaries of each slice layer;

[0032] S2. Scanning the raw material powder on each of the slice layers with a laser beam to melt the raw material powder, thereby preparing a printed workpiece for preparing a robot ankle; the spot diameter of the laser beam is d, and the scanning interval of the laser beam on each of the slice layers is H, satisfying H=(0.1~0.5)d.

[0033] In the above scheme, by limiting the spot diameter d of the laser beam and the scanning spacing H of the laser beam on each slice layer to satisfy H=(0.1~0.5)d, the raw material powder can be promoted to form columnar dislocation subcrystals, so that the prepared printed workpiece forms continuous oblique columnar dislocation subcrystals with uniform orientation, thereby changing the difficulty of plastic deformation of the printed workpiece, realizing the regulation of the wear resistance of the printed workpiece, thereby improving the wear resistance of the printed workpiece and extending the service life of the printed workpiece.

[0034] It should be noted that the scanning spacing mentioned above refers to "the distance between two adjacent scanning paths of the laser beam during the scanning process", which can also be called the scanning line spacing. In addition, in other embodiments, the printed workpiece prepared by the present application is not limited to the preparation of robot ankles. For example, it can also be used to prepare robot soles, palms and other parts. Of course, it is not limited to the field of robots, but can also be used to prepare any mechanical structure in any mechanical field.

[0035] In one embodiment, the step of melting the raw material powder on the slice layer by scanning the laser beam comprises:

[0036] The raw material powder on the first slicing layer is melted by laser beam scanning to form a first molten pool, and then the raw material powder adjacent to the raw material powder on the first slicing layer is melted by laser beam scanning to form a second molten pool; the overlap rate of the first molten pool and the second molten pool is 80%~95%.

[0037] The solidification mode of the metal material used for printing workpieces is determined by the temperature gradient and the solidification rate, and laser powder bed melting 3D printing determines that the solidification mode of the metal material is cellular solidification, and the formation of micro dislocation subcrystals is closely related to the thermal field during the solidification process. Generally, the center of the molten pool is more likely to form cellular micro dislocation subcrystals due to the small temperature gradient, while the edge of the molten pool is more likely to form columnar micro dislocation subcrystals. When the overlap rate of the first molten pool and the second molten pool exceeds 80%, the cellular dislocation subcrystals in the center of the first molten pool will be completely melted by the next new laser sintering, and the molten area is at the edge of the second molten pool formed by the next laser sintering. Therefore, the temperature gradient of the solidification process becomes larger, and the heat flow direction points from the center of the new laser spot to the edge of the molten pool, thereby promoting the formation of columnar dislocation subcrystals. Therefore, by continuously scanning and sintering layer by layer, continuous columnar micro dislocation subcrystals with uniform orientation can be formed.

[0038] It should be noted that the laser beam generates heat during the scanning process, and the heat is transferred to the powder particles to melt them and form a molten pool. Figure 3 As shown, the overlap rate R0 is expressed as the degree of overlap between two adjacent molten pools, namely the first molten pool and the second molten pool, during the laser melting process. It can be specifically expressed as the ratio of the overlapping width D0 between the first molten pool and the second molten pool to the width W of a single molten pool, that is, the overlap rate R0=D0 / W*100%.

[0039] In one embodiment, an angle between a scanning path of the laser beam on the first slicing layer and a scanning path of the laser beam on the second slicing layer is 60-90°.

[0040] In one embodiment, the spot diameter of the laser beam is 60-70 μm; and the scanning interval of the laser beam on each slice layer is 6-35 μm.

[0041] It should be noted that during the scanning process, the laser beam is usually scanned in rows and columns, and the scanning pitch refers to the distance between two adjacent rows or columns. Figure 2 As shown, the scanning paths of the laser beam in two adjacent rows or two adjacent columns of each slice layer are parallel to each other.

[0042] In one embodiment, the forming device may be an AM250 laser melting system (Renishaw AM250). Specifically, the system includes a laser and a powder spreading device. The powder spreading device can spread the raw material powder onto the substrate by a scraper. The laser emits a laser beam and scans the raw material powder according to a preset trajectory, so that the powder is melted and then condensed to obtain a printed workpiece. Of course, the types and models of the forming device are not limited to this.

[0043] In one embodiment, the power of the laser beam is 200-220 W; the scanning speed is 740-760 mm / s; the exposure time is 70-90 μs; and the dot pitch is 50-70 μm.

[0044] By limiting the power of the laser beam to the above range, the present application can ensure that the porosity inside the printed workpiece is within a relatively low range, so as to reduce the occurrence of microscopic defects such as fractures or holes. Avoid excessive power, which may cause a large amount of gas to be discharged when part of the raw material powder melts and evaporates instantly, leaving a large number of pores, thereby increasing the overall porosity; at the same time, it also avoids the failure to melt the raw material powder in time due to too low power, which may cause the spheroidized raw material powder to not be spread out in time, resulting in large pores between the raw material powders, which still leads to an increase in the overall porosity. In addition, by limiting the scanning speed to the above range, the present application avoids excessive scanning speed, which may cause part of the raw material powder to fail to melt completely, resulting in large pores between the solid phases of the unmelted raw material powder, and also avoids the scanning speed being too slow to affect the printing efficiency.

[0045] Exposure time refers to the time the laser beam stays at each point; by limiting the exposure time to the above range, it can be avoided that the exposure time is too long, which is easy to cause the evaporation of liquid metal and increase the printing time; it can also be avoided that the exposure time is too short, which makes the raw material powder not melt completely, and it is easy to cause micro defects such as fractures or holes in the printed workpiece. The point pitch refers to the distance between the centers of two adjacent light spots; by limiting the point pitch to the above range, it can be avoided that the point pitch is too large, which makes the two adjacent light spots not overlap, resulting in the raw material powder not being completely melted, making the printed workpiece prone to micro defects such as fractures or holes; it can also be avoided that the point pitch is too small, which will reduce the scanning efficiency of the laser.

[0046] In one embodiment, the raw material powder is laid with a layer thickness of 40-60 μm. This ensures that the subsequent layer of raw material powder can infiltrate the previous layer of melted raw material powder when it melts, thereby improving the interlayer bonding strength between two adjacent layers. This avoids the layer thickness being too large, which causes the laser beam to be unable to penetrate the raw material powder and affects the quality of the printed workpiece.

[0047] In one embodiment, the raw material powder includes the following elements by weight percentage: C is 0-0.003%, Ni is 12.5-13%, Mn is 0-2.00%, S is 0-0.01%, P is 0-0.02%, Cr is 17.5-18%, Cu is 0-0.50%, Mo is 2.25-2.5%, and the balance is Fe.

[0048] In one embodiment, the melting process is carried out under an inert atmosphere. Preferably, the inert atmosphere includes at least one of argon and nitrogen. Thus, the oxygen content in the environment can be reduced, oxidation during the forming process can be prevented, the surface of the printed workpiece can be smoother, crack defects on the surface can be reduced, and the tensile strength of the printed workpiece can be improved.

[0049] On the other hand, the present application also provides a workpiece, which is printed by any of the above-mentioned printing methods.

[0050] In one embodiment, the Vickers hardness (HV 0.05 ) is 235~297; the wear resistance of the workpiece is 0.145~1.470 mm 3 / (N·m).

[0051] The raw material powders used in the following Examples 1 to 4 and Comparative Example 1 all include the following elements by weight percentage: 0.001% C, 12.79% Ni, 1.44% Mn, 0.01% S, 0.01% P, 17.58% Cr, 0.15% Cu, 2.42% Mo, and the balance Fe.

[0052] Example 1

[0053] 316L stainless steel printed workpieces were obtained by laser powder bed fusion 3D printing induced by columnar dislocation subgrains:

[0054] S1. Use a computer to construct a three-dimensional model of the sample to be printed, use layered slicing software to slice the three-dimensional model, obtain contour boundary data of multiple slice layers, and transmit the contour boundary data of each slice layer to the controller of the Renishaw AM250 system; and load the raw material powder configured according to the above weight percentage into the powder spreading device of the Renishaw AM250 system, and the controller controls the powder feeding mechanism to spread the raw material powder within the contour boundary of the first slice layer.

[0055] S2. In an argon atmosphere, the raw material powder on the first slicing layer is melted by laser scanning; then the controller controls the powder feeding mechanism to lay the raw material powder within the contour boundary of the second slicing layer adjacent to the first slicing layer, and in an argon atmosphere, the raw material powder on the second slicing layer is melted by laser scanning (the laser scanning path is detailed in Figure 2 ); wherein the angle between the scanning path of the laser beam on the first slice layer and the scanning path of the laser beam on the second slice layer is 67°; the laser spot diameter is 70 μm, the laser power is 200 W, the laser scanning pitch is 30 μm, the scanning speed is 750 mm / s, the layer thickness is 50 μm, the exposure time is 80 μs, and the point pitch is 60 μm;

[0056] S3, printing all slice layers layer by layer until a 316L stainless steel printed workpiece is obtained. The printed workpiece processed in this embodiment is referred to as "Z-30".

[0057] Example 2

[0058] The difference from Example 1 is that the scanning interval of the laser is 20 μm, and the other preparation methods and conditions are the same as those of Example 1. The printed workpiece processed in this example is referred to as "Z-20".

[0059] Example 3

[0060] The difference from Example 1 is that the scanning interval of the laser is 15 μm, and the other preparation methods and conditions are the same as those of Example 1. The printed workpiece processed in this example is referred to as "Z-15".

[0061] Example 4

[0062] The difference from Example 1 is that the scanning interval of the laser is 10 μm, and the other preparation methods and conditions are the same as those of Example 1. The printed workpiece processed in this example is referred to as "Z-10".

[0063] Note: The morphology of the microstructure substructure of the 316L stainless steel printed workpiece sample obtained by printing in the above Examples 1 to 4 is as follows Figure 4 The 316L stainless steel printed workpieces formed in Examples 1 to 4 can eliminate the low wear-resistant cellular microstructures as much as possible, so that most of the microstructures are continuous columnar dislocation subgrains with uniform orientation.

[0064] Comparative Example 1

[0065] 316L stainless steel printed workpieces were obtained using ordinary laser powder bed fusion 3D printing:

[0066] S1. Use a computer to construct a three-dimensional model of the sample to be printed, use layered slicing software to slice the three-dimensional model, obtain contour boundary data of multiple slice layers, and transmit the contour boundary data of each slice layer to the controller of the Renishaw AM250 system; and load the raw material powder configured according to the above weight percentage into the powder spreading device of the Renishaw AM250 system, and the controller controls the powder feeding mechanism to spread the raw material powder within the contour boundary of the first slice layer.

[0067] S2. In an argon atmosphere, the raw material powder on the first slicing layer is melted by laser scanning; then the controller controls the powder feeding mechanism to lay the raw material powder within the contour boundary of the second slicing layer adjacent to the first slicing layer, and in an argon atmosphere, the raw material powder on the second slicing layer is melted by laser scanning (the laser scanning path is detailed in Figure 2 ); wherein the angle between the scanning path of the laser beam on the first slice layer and the scanning path of the laser beam on the second slice layer is 67°; the laser spot diameter is 70 μm, the laser power is 200 W, the laser scanning interval is 110 μm, the scanning speed is 750 mm / s, the layer thickness is 50 μm, the exposure time is 80 μs, and the point pitch is 60 μm;

[0068] S3, printing all slice layers layer by layer until a 316L stainless steel printed workpiece is obtained. The printed workpiece processed in this embodiment is referred to as "R".

[0069] Note: The morphology of the microstructure substructure of the 316L stainless steel printed workpiece sample "R" obtained by printing in Comparative Example 1 is as follows Figure 4 As shown, the microstructure substructure of the formed 316L stainless steel printed workpiece "R" mostly presents cellular dislocation subgrains.

[0070] Test Case

[0071] The 316L stainless steel printed workpiece samples obtained by printing in Examples 1 to 4 and Comparative Example 1 were subjected to wear resistance tests using a nano automatic scratch tester. The diamond indenter radius used in the test was 200 μm, the test load was 1 N, the scratch length was 5 mm, and the sliding speed was 10 mm / min.

[0072] The scratch morphology of the sample was observed by confocal microscopy (the scratch morphology is shown in Figure 2). Figure 8 The scratch depth is measured as shown in Figure 6 As shown in the figure, the wear rate of the sample is calculated from the total amount of sample and the measured amount of sample worn away (e.g. Figure 7 The Vickers hardness of the sample is calculated from the test load and the surface area of ​​the scratch (as shown in Figure 5 Before and after the wear resistance test, the samples were ultrasonically cleaned using an ultrasonic cleaning machine.

[0073] like Figure 5 As shown, the hardness of the 316L stainless steel printed workpiece obtained by laser powder bed fusion 3D printing induced by columnar dislocation subgrains in Examples 1 to 4 of the present application has been significantly improved, which is much higher than the hardness of the 316L stainless steel printed workpiece "R" obtained by ordinary laser powder bed fusion 3D printing in Comparative Example 1. Figure 6As shown, the scratch depth of the 316L stainless steel workpiece "R" obtained by ordinary laser powder bed fusion 3D printing in Comparative Example 1 is 0.984 μm, while the scratch depth of the 316L stainless steel workpiece printed by laser powder bed fusion 3D printing induced by columnar dislocation subgrains in Examples 1 to 4 of the present application is significantly reduced. Figure 7 As shown, the wear rate of the 316L stainless steel workpiece "R" printed by ordinary laser powder bed fusion 3D printing in comparative example 1 is 1.47mm 3 / (N·m), while the wear rate of 316L stainless steel printed workpieces obtained by laser powder bed melting 3D printing induced by columnar dislocation subcrystals in Examples 1 to 4 of the present application is also significantly reduced. This shows that the printed workpiece prepared by the present application can form continuous and uniformly oriented oblique columnar dislocation subcrystals, thereby changing the difficulty of plastic deformation of the printed workpiece and improving the wear resistance of the printed workpiece.

[0074] like Figure 8 As shown. In the scratch micromorphology of the 316L stainless steel printed workpiece "R" obtained by comparative example 1, not only a large number of slip lines but also pits appeared; while in the scratch micromorphology of the 316L stainless steel printed workpiece obtained by examples 1 to 4 of the present application, no pits appeared. This is because the 316L stainless steel printed workpiece "R" prepared in comparative example 1 forms a large number of cellular microstructural substructures. Under the action of external loads, the material undergoes plastic deformation, microscopic slippage occurs, and slip lines appear. The slip lines gradually expand to form cracks. As the cracks continue to extend, material fragments peel off and wear debris is formed, thereby causing the formation of pits in the wear area. This will affect the wear resistance of the printed workpiece "R".

[0075] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

Claims

1. A method for improving the wear resistance of a robot ankle by 3D printing, characterized in that: include: Constructing a three-dimensional model of a sample to be printed, slicing the three-dimensional model to obtain contour boundaries of multiple slice layers, and laying raw material powder within the contour boundaries of each slice layer; The raw material powder includes the following elements by weight percentage: C is 0-0.003%, Ni is 12.5-13%, Mn is 0-2.00%, S is 0-0.01%, P is 0-0.02%, Cr is 17.5-18%, Cu is 0-0.50%, Mo is 2.25-2.5%, and the balance is Fe; The multiple slicing layers include a first slicing layer and a second slicing layer disposed adjacent to the first slicing layer; an angle between a scanning path of the laser beam on the first slicing layer and a scanning path of the laser beam on the second slicing layer is 67°; The raw material powder on the first slice layer is melted by laser beam scanning to form a first molten pool, and the raw material powder adjacent to the raw material powder on the first slice layer is melted by laser beam scanning to form a second molten pool, wherein the overlap rate between the first molten pool and the second molten pool is 80% to 95%, wherein the laser power is 200 to 220 W, the laser spot diameter is 60 to 70 μm, and the laser scanning interval is 10 μm to 30 μm, thereby preparing a printed workpiece for preparing a robot ankle; The spot diameter of the laser beam is d, and the scanning interval of the laser beam on each slice layer is H, satisfying H=(0.1~0.5)d.

2. The method according to claim 1, characterized in that The scanning speed of the laser beam is 740-760 mm / s; the exposure time is 70-90 μs; and the dot pitch is 50-70 μm.

3. The method according to claim 1, characterized in that The layer thickness of the raw material powder is 40-60 μm.

4. The method according to claim 1, characterized in that: The melting process is carried out under inert atmosphere.

5. A workpiece, characterized in that: The method is obtained by processing according to any one of claims 1 to 4.

6. The workpiece according to claim 5, characterized in that The Vickers hardness (HV 0.05 ) is 235~297; the wear resistance of the workpiece is 0.145~1.470 mm 3 / (N·m).

Citation Information

Patent Citations

  • High-strength wear-resistant corrosion-resistant steel powder for additive manufacturing and additive manufacturing method

    CN112077300A